A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq - Safaei-Mahroo, Barbod; Ghaffari, Hanyeh; Ghafoor, Aram; Amini, Saywan (Zootaxa, 2017)
We describe a new species of gecko of the genus Hemidactylus from the oak woodlands of Zagros Forest Steppe of Qara Dagh Mountains, Sulaimani, northeastern Iraq, based on morphological and molecular characteristics. Hemidactylus kurdicus sp. nov. is distinguished from all other related Arid clade Hemidactylus species in the Middle East by having a single pair of postmental scales; it differs H. turcicus, H. robustus, H. ulii, H. sinaitus, H. shihraensis and H. yerburii based on the number of lamellae under the first and fourth toes of pes. Mitochondrial DNA including CytB and 12S identify a consistent divergence between H. kurdicus and H. persicus. An identification key to the genus Hemidactylus in Iraq is presented.